The impact of apathy on cognitive performance in the elderly - Montoya‐Murillo, Genoveva; Ibarretxe‐Bilbao, Naroa; Peña, Javier; Ojeda, Natalia (International journal of geriatric psychiatry, 2019)
Objectives To examine the impact of apathy on cognitive performance in the elderly following the conceptual principles proposed by Marin1 and Stuss et al2 and to determine the role of the symptoms of apathy in different cognitive domains. Methods Cross‐sectional study with a cohort of healthy elderly subjects over 55 years old (n = 140). One hundred forty healthy‐elderly subjects (aged 79.24 ± 8.6 years old) were recruited from 12 day centers in Northern Spain. Participants underwent a neuropsychological battery, which evaluated Mini Mental State Examination (MMSE), attention, processing speed, verbal fluency, visual and verbal memory, working memory, and executive functioning. Apathy was assessed by the Lille Apathy Rating Scale (LARS), which is composed of four factors: intellectual curiosity, emotion, action initiation, and self‐awareness. Correlation and linear regression analyses were performed. Results In the correlational analysis, the LARS total score correlated negatively with global cognition, verbal fluency, and visual and verbal memory. The intellectual curiosity factor correlated negatively with all cognitive domains except attention. The emotion factor correlated negatively with visual memory. No correlation was found between the action initiation and self‐awareness factors or any of the cognitive variables. Multiple stepwise regression analysis showed that symptoms of apathy explained cognitive performance in attention, processing speed, verbal fluency, visual and verbal memory, working memory, executive functioning, and MMSE. Conclusions Apathy was significantly associated with cognitive performance, especially with the intellectual curiosity factor. Our results suggest that specific symptoms of apathy contribute differently to individual cognitive domains.